2022
DOI: 10.1093/hmg/ddac236
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and cell-specific whole-transcriptome meta-analysis from brain and retina reveals differential expression of dystrophin complexes and new dystrophin spliced isoforms

Abstract: The large DMD gene encodes a group of dystrophin proteins in brain and retina, produced from multiple promoters and alternative splicing events. Dystrophins are core components of different scaffolding complexes in distinct cell types. Their absence may thus alter several cellular pathways, which might explain the heterogeneous genotype–phenotype relationships underlying central comorbidities in Duchenne muscular dystrophy (DMD). However, the cell-specific expression of dystrophins and associated proteins (DAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…However, since we observed fewer proliferating OPCs during increased expression of SOX2, additional molecular changes are probably involved, which lead to OPC alterations. One possibility is that loss of dystrophin affects the number of astrocytes, which also express dystrophin ( Nico et al, 2003 ; Garcia-Cruz et al, 2023 ). However, we did not observe changes in levels of GFAP, widely used a marker for astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since we observed fewer proliferating OPCs during increased expression of SOX2, additional molecular changes are probably involved, which lead to OPC alterations. One possibility is that loss of dystrophin affects the number of astrocytes, which also express dystrophin ( Nico et al, 2003 ; Garcia-Cruz et al, 2023 ). However, we did not observe changes in levels of GFAP, widely used a marker for astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed dystrophin expression in multiple areas of the brain, including neurons, astrocytes and oligodendrocytes (OLs) ( Hoffman et al, 1988 ; Miike et al, 1989 ; Gorecki et al, 1991 ; Bies et al, 1992 ; Yoshioka et al, 1992 ; Lidov et al, 1993 ; Tokarz et al, 1998 ; Garcia-Cruz et al, 2023 ; Aranmolate et al, 2017 ), yet the cell and molecular mechanisms that contribute to neurological deficits in DMD remain largely unexplored. In addition, dystrophin expression in the brain appears to be highly complex, with different dystrophin gene products being regulated both spatially and temporally ( Garcia-Cruz et al, 2023 ; Romo-Yanez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of precursor messenger RNA and alternative RNA splicing play a crucial part in the post-transcriptional regulation of gene expression. For example, the sarcoplasmic reticulum Ca 2+ -ATPase exists in the form of several protein Some genes that contain protein-coding sequences for the production of musclespecific components, such as the extremely large X-chromosomal DMD gene that encodes the Dp427-M isoform of the membrane cytoskeletal protein named dystrophin, have more than one promoter [282] (Figure 9). Thus, several protein products with tissuespecific expression patterns can derive from the sequence information that is stored in one individual gene.…”
Section: Proteomic Complexity In Skeletal Musclesmentioning
confidence: 99%
“…The resulting dystrophin proteins (Dp) have been named according to their molecular mass. So far, the described proteins include Dp427 (full-length dystrophin), Dp260, Dp140, Dp116, Dp71, and Dp40, which are found in different tissues, such as the brain, muscle, retina, kidney, peripheral nerves, liver and lung [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%